PENERAPAN KODE ETIK JURNALISTIK ISLAMI DI ERA MILENIAL - Suf Kasman (Jurnal Komodifikasi, 2019)
Journalism ethics and standards comprise principles of ethics and of good practice as applicable to the specific challenges faced by journalists. This subset of media ethics is widely known to journalists as their professional "code of ethics" or the "canons of journalism".  How do journalists decide what news to write each day? How do they convey the science of a politicized issue like climate change? How do they decide when to print national secrets? The answers to all of these questions are informed by journalistic ethics, which guide reporters and editors to seek out the truth and act with integrity.Journalism ethics and standards comprise principles of ethics and of good practice as applicable to the specific challenges faced by journalists. This subset of media ethics is widely known to journalists as their professional "code of ethics" or the "canons of journalism".  How do journalists decide what news to write each day? How do they convey the science of a politicized issue like climate change? How do they decide when to print national secrets? The answers to all of these questions are informed by journalistic ethics, which guide reporters and editors to seek out the truth and act with integrity.